P-152 What do we know about 'human factors' in palliative care?. (19th November 2022) - Gray, Alice; Freshwater, Sarah; Birkinshaw, Jamie
Abstract : Background: Human Factors (HF) is a discipline that is recognised to be beneficial to maintaining patient safety and quality improvement within healthcare settings. We aimed to understand what literature there was around the use of HF principles in palliative care and then evaluate what palliative care staff had experienced of HF training and application to practice. Methods: We performed a literature review of which there were no papers relevant to our study. This was followed by a survey of palliative care clinicians in the West Midlands reviewing their knowledge and experiences of HF. Results: A total of 137 respondents completed the survey, with a mixture of working environments and staff groups. A small majority of respondents had encountered HF prior to the survey, with hospice staff demonstrating a majority not previously aware of HF and 76% of total respondents had no formal training. Medical staff demonstrated particularly high awareness and training in HF, whilst within nursing staff only a minority had either. Only a minority of respondents were aware of a HF approach being used in their workplaces although the largest proportions of those aware of such an approach came from Allied Health Professionals, and was more common in staff working in dual locations. Conclusions: This study demonstrates that understanding or awareness of HF amongst different staff groups and settings is very variable. An understanding of HF amongst staff is likely to be beneficial in multiple ways, not least in terms of supporting the identification of potential sources of error and empowering staff in assessing their own approaches, as well as those around them. We recommend that the benefits of staff having a HF awareness and understanding be examined in more detail for impacts on patient care, safety and system efficiency.